2017
DOI: 10.1136/sextrans-2015-052511
|View full text |Cite
|
Sign up to set email alerts
|

Chlamyweb Study I: rationale, design and acceptability of an internet-based chlamydia testing intervention

Abstract: AFFSAPS n° IDRCB 0211-A01000-41; pre-results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“… 13 15 24 25 An observational study linked to the French RCT reported similar findings to our study. 26 In Sweden, a similar online service saw 74.5% of kits returned by a majority of female users and young people aged <25 years. 25 Studies in the UK and the USA have reported high use of online services among BME, low-income groups and MSM and high positivity, but lower return rates.…”
Section: Discussionmentioning
confidence: 99%
“… 13 15 24 25 An observational study linked to the French RCT reported similar findings to our study. 26 In Sweden, a similar online service saw 74.5% of kits returned by a majority of female users and young people aged <25 years. 25 Studies in the UK and the USA have reported high use of online services among BME, low-income groups and MSM and high positivity, but lower return rates.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 7000 individuals who will receive the kit, we assumed that 70.00% (4900/7000) will return their DBS on filter paper, corresponding to 35% of the eligible Health Barometer participants. The 70.00% (4900/7000) return rate was based on the 68% and 62% participation rates in 2 French home-screening studies for chlamydia infections [ 19 , 22 ] and on the hope that our thorough system of reminders would maximize the rate of return.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals may therefore wish to anonymously evaluate for themselves whether they are at increased risk. Access to online, self-administrable, web-based quizzes that enable participants to determine their risk for HIV/STI remain limited in Germany although similar services have been reported within the framework of public sector sexual health care in Canada, the United States, Australia, and some European countries including France and the United Kingdom [4][5][6][7][8][9]. Further, the availability of such Online Risk Tests supports continual surveys that strategize sexual and reproductive health services.…”
Section: Introductionmentioning
confidence: 99%